USE OF THE METHOD OF AGAR PLATES FOR THE ASSESSMENT OF FUNGICIDE EFFICIENCY TO THE FUNGI OF FUSARIUM TYPE - N. N. Dubrovskaya; V. V. Chekmarev (Зерновое хозяйство России, 2018)
The diseases of fusarium etiology annually damage agricultural crops, decreasing their yields and quality of products. Fusarium of a head is the most dangerous. The disease decreases the plant productivity and makes grain unsuitable for food and feed purposes. Many countries face the problem to grow the crops free of mycotoxins, resulted from the existence of the fungi of Fusarium type. Grain crop cultivation, resistant to the infection with the fungi can be a good solution of the problem. But there are only a few crops tolerant to the disease. Their resistance to the pathogens does not remain permanent and constantly decreases because of new virulent strains and the change of the varietal composition of the pathogens. For this reason, it’s very urgent to develop and screen the chemicals, which are effective against fusarium infection. The field trials of new and applied in production means of plant protection allow estimating their efficiency. As it takes a really long time, it’s possible to use the method of agar plates to speed the chemicals testing. The method is not as precise as the trials because of the absence of the first component in the system of correlation ‘plant-pathogen-fungicide’. But it allows estimating the efficiency of fungicide to pathogenic fungi. The application of the method of agar plates gave the opportunity to establish the most efficient (90,1-100,0 %) chemicals to the fungi of Fusarium acuminatum, F. culmorum and F. sporotrichioides; they are ‘Sportak’, ‘Optimo’, ‘Falkon’, ‘Folokur’ and ‘Fundazol’. The first of them was the most effective (97.2 -100.0 %) against all studied types of fungi. The method can be used for preliminary evaluation of fungicides and resistance of the fungi of Fusarium type to them.